The Role Of Taste Image And Popularity Of The Taliwang Bersaudara Chicken Restaurant In South Jakarta As The Culinary Identity Of Lombok, West Nusa Tenggara - Aprilia, Melinda; Demolingo, Ramang H. (Ann Publisher, 2025)
The shift of traditional food to urban environments is a clear example of cultural interaction in the modern era. A Lombok specialty, Ayam Taliwang Bersaudara (South Jakarta's Ayam Taliwang Brothers), remains relevant to the preferences of Jakartans. The purpose of this study was to examine how the flavor and popularity of Ayam Taliwang Bersaudara Restaurant contribute to Lombok's culinary identity, as well as the adaptation strategies used to remain authentic and relevant in the market. Qualitative descriptive data collection methods used observation, documentation, and in-depth interviews. A qualitative SWOT analysis was used to identify the strengths, weaknesses, opportunities, and threats affecting the restaurant's sustainability. The use of Lombok raw materials and traditional cooking methods maintains the authentic flavor, according to the study. The level of spiciness and effective word-of-mouth approach are tailored to the market. The balance between contextual innovation and cultural preservation is crucial for the restaurant's success. The results indicate that maintaining the sustainability of traditional culinary in urban areas requires collaboration between managers, the community, and the government.